The Effectiveness of the Single Identity Number System: An Exploratory Study on Using NIK as NPWP by Individual Taxpayers - Sumule, Esther Tinggi; Toding, Yupsari; Delki, Delki; Pasanda, Erna; Beloan, Bertha (Journal of Development Research, 2025)
This study aims to determine whether the Population Identification Number (NIK) system, when used as a Taxpayer Identification Number (NPWP), is effective from the perspective of individual taxpayers. The research employed a descriptive qualitative method, using purposive sampling to select informants. The informants consisted of individual taxpayers working in various public and private institutions, and data were collected through in-depth interviews. The results indicate that the integration of NIK into NPWP is considered effective for implementation in Indonesia. This integration facilitates individual taxpayers in fulfilling their tax rights and obligations. Furthermore, the policy is viewed as a means of simplifying tax administration and improving taxpayer compliance. In conclusion, using NIK as NPWP has the potential to serve as an effective solution for tax administration reform in Indonesia, particularly in promoting efficiency and enhancing individual taxpayer compliance.